Current research in obstetrics and gynecology - Pacheco-Romero, José (2018)
Research within the specialties of Obstetrics and Gynecology is impacting, and tries to solve many of today’s clinical problems. In these pages, we present summaries of abstracts of current research published in institutional documents and in important magazines of our specialty. References are included.